The Clock in the Living Room: Re-Imagining Social Connection through Intergenerational Listening in the COVID-19 Crisis - Levesque, Lauren Michelle; Levesque, J.R.F. (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2022)
This article explores the practice of intergenerational listening and its implications for re-imagining social connection in the COVID-19 crisis. Using an approached based in conversation and exchange facilitated through video-conferencing platforms, the authors critically reflect on the possibilities for developing a new sense of social connection by listening to the everyday sounds (Tuuri and Peltola 2019) of particular spaces. More specifically, the principal aim is to investigate the impact of re-imagining the daily sounds of spaces under locked-down as sources of intimacy, accompaniment, and creativity. These sounds include the ‘buzz’ of a cherished clock, the creak of a screened in porch, or records regularly listened to in a family living room. Supported by literature on ‘listening at a distance’ (Finer 2018) and the ‘sonic imagination’ (Street 2019), we ask: how can intergenerational, socially-distanced listeners engage with sound and space to improvise new forms of social connectivity? Asking these questions, we argue, can inform research and action into the roles that intergenerational listening and improvisation can play in the representation and the valuing an ageing population (Lanphier 2019) in an emerging post-pandemic musical landscape.